A lucky American childhood - Engle, Paul, 1908-1991 (Singular lives., 1996)
More than any other individual, Paul Engle was the spirited force behind the creative writing workshops now so abundant in America. His indomitable nature, enthusiasm, and great persuasive powers, coupled with his distinguished reputation as a poet, loomed large behind the founding of the influential Iowa Writers' Workshop. A Lucky American Childhood will appeal to people with memories of the small-town America that Paul Engle describes with such affectionate realism and to all those interested in the roots of this renowned man of letters.